2015
DOI: 10.1073/pnas.1508815112
|View full text |Cite
|
Sign up to set email alerts
|

Metformin increases degradation of phospholamban via autophagy in cardiomyocytes

Abstract: Phospholamban (PLN) is an effective inhibitor of the sarco(endo) plasmic reticulum Ca 2+ ATPase (SERCA). Here, we examined PLN stability and degradation in primary cultured mouse neonatal cardiomyocytes (CMNCs) and mouse hearts using immunoblotting, molecular imaging, and [ 35 S]methionine pulse-chase experiments, together with lysosome (chloroquine and bafilomycin A1) and autophagic (3-methyladenine and Atg5 siRNA) antagonists. Inhibiting lysosomal and autophagic activities promoted endogenous PLN accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 52 publications
1
42
0
Order By: Relevance
“…The affinity of PLN to SERCA2 is significantly influenced by phosphorylation of PLN. Furthermore, initial studies have revealed that triggered degradation of PLN by autophagy or the ubiquitin-proteasome system may play an additional regulatory role [49][50][51]. However, an involvement of intramembrane proteases in the control of PLN as we report it here has not been reported before.…”
mentioning
confidence: 56%
“…The affinity of PLN to SERCA2 is significantly influenced by phosphorylation of PLN. Furthermore, initial studies have revealed that triggered degradation of PLN by autophagy or the ubiquitin-proteasome system may play an additional regulatory role [49][50][51]. However, an involvement of intramembrane proteases in the control of PLN as we report it here has not been reported before.…”
mentioning
confidence: 56%
“…Metformin is a first‐line antidiabetic drug that also activates autophagy and has cardiovascular protective effects (Song et al, ; Teng et al, ), although recent study has reported that metformin fails to cardioprotective effect in nonaging I/R swine models (Techiryan et al, ). In the present study, we found that metformin treatment effectively reduced I/R‐induced necroptosis in aging hearts, improved cardiac function after myocardial infarction, and improved long‐term survival.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is of paramount importance in the clearance of stress‐induced protein aggregates and aggresomes in cardiomyopathies . Recently, it has been shown, in primary cultured neonatal mouse cardiomyocytes, that PLN is degraded by selective p62‐mediated autophagy after polyubiquitinylation . p62 acts as an adaptor protein during aggregation, sequestration [hence its synonym, sequestosome‐1 (SQSTM‐1)] and degradation of misfolded proteins by the ubiquitin–proteasome pathway and selective autophagy .…”
Section: Introductionmentioning
confidence: 99%